Virtual screening and enzymatic inhibition analysis of bacterially expressed lactate dehydrogenase from plasmodium knowlesi for antimalarial drugs development - Nurhanis Ogu Salim (Kulliyyah of Engineering, International Islamic University Malaysia, 2021)
Malaria is a mosquito-borne tropical disease caused by parasite of the Plasmodium genus. Globally, about 229 million cases of malaria with approximately 409 000 mortalities occurred in 2019. In Malaysia, Plasmodium knowlesi has now become the most common cause of malaria in the country. Disease management remains challenging due to malaria parasites resistance towards the current antimalarial agents, which is one of the factors that prevent the elimination of malaria. Hence, new drugs to treat malaria specifically caused by P. knowlesi should be a priority in malaria research. Selection of antimalarial candidates via virtual screening, which specifically targets enzymes such as lactate dehydrogenase (LDH) in glycolytic pathway of Plasmodium is a good strategy because it is the sole energy producer during erythrocytic cycle of the parasites. The aim of this study is to screen for novel antimalarial candidates via virtual screening and to evaluate the effects of the selected virtually screened compounds on the activity of LDH by inhibition studies. The potential compounds were screened via computational approach comprising Ligand-Based Drug Design using Ultra-Fast Shape Recognition with Atom Types (UFSRAT) and Ultra-Fast Shape Recognition with CREDO Atom Types (USRCAT), followed by structure-based drug design using Autodock4 programme. UFSRAT have resulted with similarity scores ranged from 0.832-0.914 for compounds that most resemble oxamate, a known LDH inhibitor. Meanwhile, USRCAT similarity scores for compounds that most resemble pyruvate (substrate) and lactate (product), ranged from 0.859 to 0.882 and 0.822 to 0.849, respectively. Structure-based drug design for analogues of oxamate, pyruvate and lactate have resulted with minimum binding energies ranged from -3.59 kcal/mol to -0.07 kcal/mol, -5.25 kcal/mol to -1.99 kcal/mol and -3.74 kcal/mol to -2.81 kcal/mol respectively. Meanwhile, cloning of P.knowlesi lactate dehydrogenase (Pk-LDH) gene into expression vector (pET21a) was performed, prior to protein expression in bacterial system. SDS-PAGE analyses revealed that a fusion protein of ~34 kDa was present in soluble fraction, which confirmed size of the bacterially-expressed Pk-LDH and then was subsequently purified to homogeneity using Immobilized Metal Ion Affinity Chromatography (IMAC) and Size Exclusion Chromatography (SEC). Protein characterization was performed to verify the identity of purified proteins using Matrix-Assisted Laser Desorption Ionization-Time of Flight (MALDI-TOF) mass spectrometry, results confirmed that bacterially-expressed Pk-LDH obtained in this study is similar to P. knowlesi LDH with 282 protein sequence coverage. The structural properties of Pk-LDH protein were investigated by using far UV Circular Dichroism (CD) Spectroscopy, where proper folding and correct disulfide linkages in the pure Pk-LDH enzyme were verified. The specific activity of the purified Pk-LDH enzyme was found to be 475.6 U/mg, confirming the presence of pure and active protein. Finally, selected compounds obtained from in silico screening were tested on purified Pk-LDH via enzymatic inhibition assay and the compound namely oxalic acid has shown 54.12% of inhibition with an IC50 value of 0.6398 mM,the most potent compared to other compounds. This study has therefore resulted in the development of a reliable method for producing soluble Pk-LDH that is biologically-active and leads to further exploration of the potential compounds that can be developed as promising antimalarial drugs, specifically to treat malaria infections caused by P. knowlesi.